An in-situ modification method for coal roadways with heightened burst risk - Ouyang, Zhenhua; Li, Gen; Wang, Qiong; Yi, Haiyang; Li, Zhengsheng; Shi, Qingwen (Frontiers in Earth Science, 2023)
It is hard to control roadways effectively with a heightened burst risk using conventional support techniques, which may cause burst fatalities in the coal mine. Thus, an in-situ modification method, which involves artificially constructing a cracked zone and a reinforced zone, was proposed to improve the stability of the roadways with heightened burst risk. This paper investigated the efficiency to non of the in-situ modification method in improving burstroadway safety by performing a physical experiment. The results of the experiment indicated that the dynamic stress was obviously reduced in the modified roadway. Accordingly, the influence factors of the in-situ modification method were explored using numerical simulation. It was found that the thickness and the degree of damage to the cracked zone were key governing factors in reducing energy and improving roadway stability. The energy dissipation value increased as the thickness and the degree of damage to the cracked zone increased but showed a slower growth trend when the thickness and the degree of damage to the cracked zone increased to a certain value. In addition, the high sensitivity to dynamic load was found in parts of the roadway side exhibiting a larger stress reduction rate even with thinner cracked zone thickness and a lower degree of damage. This research provides an effective and economical method for coal roadways with heightened burst risk.